(untitled) (Research, Society and Development, 2021)
Due to the different possibilities of psychology in special education, an exploratory study was carried out on the perception of psychologists (n = 64) and psychology students (n = 70) about this area. Participants answered a questionnaire containing two parts. The first had six open questions, and the second, 14 myths associated with giftedness. The results indicated, in general, gaps in training to work in the subject, to demonstrate little preparation to work in this area due to the limited presence of disciplines and, consequently, the lack of knowledge of professional practices. Professionals and students indicated the belief in false myths. Participants also reported that they do not feel prepared to work with this audience, especially gifted individuals. Overall, the study indicated the importance of reformulating psychology training to work in ​​special education so that its professionals feel prepared to deal with this specific audience that they may be asked to attend in their professional practice.